A RANDOMIZED CONTROLLED STUDY TO ASSESS THE EFFICACY OF ABHAYAM GHRITHA, VACAYASHTYAHWADI CHOORNA AND SPEECH THERAPY IN CHILDREN WITH DELAYED LANGUAGE MILESTONES - Nazeema P K; Chitta Ranjan Das (International Journal of Applied Ayurved Research, 2021)
Background: Developmental disabilities are now a matter of global public health concern. With the increasing prevalence of developmental disabilities, benefits of early interventional services are inevitable to lessen the burden of associated behavioral problems. In India, Ayurveda significantly outstands among the complementary and alternative systems of medicine. Hence the study is proposed to determine the effectiveness of Ayurveda intervention in children with delayed language milestones. Methods Ninety children with speech and global developmental delay will be enrolled in a randomized controlled trial to three groups. The primary outcome measure was the Receptive-Expressive Emergent Language scale (REELS) and secondary outcome measures include improvement in Social and communication skill, concentration and attention level with improvised school performance through Denver Development Scale. Interventions will be continued for three months and assessments were made on 30th day, 60th day, 90th day with a follow up assessment on 120th day after intervention. Intention to treat design was used to analyze the data collected. Expected Outcome The anticipated outcome of the trial is to enhance the reversal of speech developmental delay through ayurveda interventions, with beneficial effects on behavioral, social and communication skills of the children. Discussion The holistic approach of ayurveda through combined treatment module incorporating medicinal interventions like Abhayam Ghritham, Vachayashtyahwadi Choornam and speech therapy helps in improving the quality of life of the child along with treatment for the affected domain.